2021
DOI: 10.7717/peerj.12349
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis reveals candidate genes for male sterility in Prunus sibirica

Abstract: Background The phenomenon of male sterility widely occurs in Prunus sibirica and has a serious negative impact on yield. We identified the key stage and cause of male sterility and found differentially expressed genes related to male sterility in Prunus sibirica, and we analyzed the expression pattern of these genes. This work aimed to provide valuable reference and theoretical basis for the study of reproductive development and the mechanisms of male sterility in Prunus sibirica. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In addition to the above-mentioned pathways, results in this experiment also revealed that the “starch and sucrose metabolism” and “glycolysis/glycogenesis” pathways were also altered in W99A. These two pathways are essential for the energy production in organisms, of which the abnormalities may interfere with the energy metabolic processes in mitochondria and finally result in male sterility [ 41 ]. In pepper, the contents of ATP and NADH significantly decreased in the maintainer line during the abortion stage of pollen [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above-mentioned pathways, results in this experiment also revealed that the “starch and sucrose metabolism” and “glycolysis/glycogenesis” pathways were also altered in W99A. These two pathways are essential for the energy production in organisms, of which the abnormalities may interfere with the energy metabolic processes in mitochondria and finally result in male sterility [ 41 ]. In pepper, the contents of ATP and NADH significantly decreased in the maintainer line during the abortion stage of pollen [ 42 ].…”
Section: Discussionmentioning
confidence: 99%